THE STATE PRESIDENT’S UNIT IN ITS CAPACITY AS CEREMONIAL GUARD - Meyers, E.M. (Scientia Militaria - South African Journal of Military Studies, 2012)
The most important function of the State President’s Guard is that of acting as home guard for the State President and of acting as guard of honour at ceremonial occasions. Members of such a special guard not only had to meet specific requirements in the past. but even today they are subject to strict selection requirements. The uniform of the State President’s Guard was changed recently. The new uniform, based on the current army uniform, replaces the old Republican model.